2020
DOI: 10.3390/pr8121578
|View full text |Cite
|
Sign up to set email alerts
|

Whispering-Gallery-Mode for Coherent Random Lasing in a Dye-Doped Polystyrene Encapsulated Silica-Glass Capillary

Abstract: Dye-doped polystyrene (DDPS) encapsulated in a silica-glass capillary with a diameter of 300 μm was fabricated through radical polymerization of styrene within the capillary. The coherent random lasing (RL) with full width at half maximum (FWHM) of 0.36 nm and a quality factor of 1608 was produced in the DDPS with the capillary when pumping at 532 nm. However, the incoherent RL with FWHM of 6.62 nm and a quality factor of 92 was produced in the DDPS without the capillary. A detailed investigation on this pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…42 For instance, Nie et al reported a dye-doped polystyrene-encapsulated silica-glass capillary, in which a strong WGM resonance in the capillary helps the generation of coherent RL when the refractive index of the filling medium is greater than that of the glass capillary. 43 Chen et al modified SiO 2 nanospheres in the surface of ZnO nanorods, pumping out a random laser with the aid of the WGM resonance effect of spherical particles. 44 Furthermore, in 2021, Shi et al proposed a spectral encryption approach based on selectively visualized spectral modes in RL by coupling them with an external WGM cavity.…”
Section: Introductionmentioning
confidence: 99%
“…42 For instance, Nie et al reported a dye-doped polystyrene-encapsulated silica-glass capillary, in which a strong WGM resonance in the capillary helps the generation of coherent RL when the refractive index of the filling medium is greater than that of the glass capillary. 43 Chen et al modified SiO 2 nanospheres in the surface of ZnO nanorods, pumping out a random laser with the aid of the WGM resonance effect of spherical particles. 44 Furthermore, in 2021, Shi et al proposed a spectral encryption approach based on selectively visualized spectral modes in RL by coupling them with an external WGM cavity.…”
Section: Introductionmentioning
confidence: 99%